Compatibility of large ELM control and stable partial detachment with neon/argon seeding in EAST. (1st February 2023) - Li, K.; Lin, X.; Yang, Z.; Yang, Q.; Xu, G.; Meng, L.; Wang, Y.; Lan, H.; Zhang, B.; Xu, L.; Wu, K.; He, T.; et al.
Abstract: It is necessary to achieve simultaneous exhaust of excessive transient and steady-state heat fluxes on the divertor target for the divertor protection in the future fusion reactors. The sustained large ELM control and stable partial detachment have been achieved concurrently with argon (Ar) or neon (Ne) seeding in EAST. With Ne seeding, the large ELMs with frequency f ELM ∼ 100 Hz disappear and a stable ELM-free state with H 98, y 2 > 1 is maintained. Meanwhile, the electron temperature T et around the lower outer strike point decreases from more than 70 eV during the large ELM burst to less than 5 eV in the stable ELM-free phase. In addition, a slight improvement of plasma confinement is observed in the partially detached state, mainly attributed to the increased electron density n e and ion temperature T i in the core region. In the pedestal region, the density gradient and the electron temperature show subtle variation. The effective charge number Z eff increases significantly after Ne seeding, leading to a decrease in the edge bootstrap current and the pedestal pressure gradient, and thus the stabilization of ELMs. With Ar seeding, the large ELMs are also suppressed at first, but soon transit to type-III ELMs with a high f ELM ∼ 1 kHz, highly correlated with the energy confinement degradation. The steady-state and transient heat fluxes on the divertor can be both well reduced with Ar/Ne seeding in EAST.